Building a Health Research Relationship Between First Nations and the University in Manitoba - O’Neil, John (Can J Public Health, 2005)
This paper describes the emergence of a formal partnership between Manitoba First Nations and researchers in the Department of Community Health Sciences at the University of Manitoba. This partnership reflects two decades of a working relationship in Manitoba involving university researchers and First Nations communities, as well as new and innovative approaches to developing organizations, training initiatives and projects that strengthen First Nations principles of governance. The emerging trust that has developed between the Manitoba First Nations and the University has made it possible to extend this partnership into building further research capacity and evidence-based decision-making among First Nations. Discussions between the Assembly of Manitoba Chiefs and the Northern Health Research Unit resulted in the development of a Manitoba First Nations Centre for Aboriginal Health Research. Its mission is to initiate, coordinate and support research activities designed to assist First Nations and Aboriginal communities and organizations in their efforts to promote healing, wellness and improved health services in their communities. Much of the health research described in this journal was facilitated through this partnership, which demonstrated the value of partnerships and new funding opportunities to better address the health information needs of First Nations communities, particularly at a time when Aboriginal communities were highly skeptical of the value of academic research.